Integrating UAVs into the Cloud Using the Concept of the Web of Things. (15th October 2015) - Mahmoud, Sara; Mohamed, Nader; Al-Jaroodi, Jameela
Abstract : UAVs, Unmanned Aerial Vehicles, have gained significant attention recently, due to the increasingly growing range of applications. Most UAVs use radio frequency transmission to communicate with the ground station to receive commands and send data. However, this model of communication restricts the user to being in specific locations and limits missions to narrow areas. This paper proposes a Cloud Computing (CC) integration where the UAVs become part of the cloud infrastructure and can be accessed ubiquitously. This concept is similar to the Internet of Things (IoT) where smart objects are connected to the Internet and are given unique identification. Moreover, to provide an appropriate way of communication, UAV resources are developed as web services. They provide their resources and services through a uniform interface using the RESTful HTTP architecture. This concept is relevant to the Web of Things (WoT) that provides smart objects with interfaces to be accessed through the World Wide Web (WWW). However, in UAVs, not only the web services are computational services but they are also physical elements affecting and affected by the real world environment.